2021
DOI: 10.2147/rmhp.s301645
|View full text |Cite
|
Sign up to set email alerts
|

Development and Psychometric Properties of the Health Belief Scales Toward COVID-19 Vaccine in Ho Chi Minh City, Vietnam

Abstract: Background Beliefs of an individual about health conditions can play an important role in contributing to their behavior concerning good and bad health practices. The aim of this study was to develop and assess a set of vaccination belief scales in relation to COVID-19 vaccines. Methods A cross-sectional study was conducted between July 2020 and January 2021 using a systematic random sampling of 425 adult outpatients at two hospitals in Ho Chi Minh City, Vietnam. An ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 27 publications
3
15
0
1
Order By: Relevance
“…Multivariable analysis revealed that HBM constructs were associated with vaccination intention in the Philippines, which is in accordance with other studies from the Asia-Pacific region (Wong et al, 2020, 2021; Lin et al, 2020; Yu et al, 2021; Kabir et al, 2021; Huynh et al, 2021; Tao, Wang & Liu, 2021) Perceptions of high susceptibility, high severity, and significant benefits were all good predictors for vaccination intent. A study to interrogate vaccine hesitancy among Filipinos in two urban communities in Manila before the COVID-19 pandemic also found that respondents who believed in the protective nature of vaccines were less likely to report vaccine hesitancy and were nine times less likely to refuse vaccination for their children because of negative media exposure (Migriño et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Multivariable analysis revealed that HBM constructs were associated with vaccination intention in the Philippines, which is in accordance with other studies from the Asia-Pacific region (Wong et al, 2020, 2021; Lin et al, 2020; Yu et al, 2021; Kabir et al, 2021; Huynh et al, 2021; Tao, Wang & Liu, 2021) Perceptions of high susceptibility, high severity, and significant benefits were all good predictors for vaccination intent. A study to interrogate vaccine hesitancy among Filipinos in two urban communities in Manila before the COVID-19 pandemic also found that respondents who believed in the protective nature of vaccines were less likely to report vaccine hesitancy and were nine times less likely to refuse vaccination for their children because of negative media exposure (Migriño et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, several studies have shown that the HBM constructs can serve as an important predictor of influenza vaccination uptake (Brewer et al, 2007; Shahrabani, Benzion & Yom Din, 2009; Shahrabani & Benzion, 2010; Tsutsui, Benzion & Shahrabani, 2012). During the COVID-19 pandemic, the HBM was used to assess the root causes of COVID-19 vaccine hesitancy in the Asia-Pacific region and beyond (Wong et al, 2020, 2021; Lin et al, 2020; Yu et al, 2021; Kabir et al, 2021; Shmueli, 2021; Huynh et al, 2021; Tao, Wang & Liu, 2021; Mahmud et al, 2021; Banik et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The self-administered questionnaire included the following sections: (1) the demographics of participants, (2) the 12-items of the HBM scale which was calculated for validity and reliability from our preliminary study, with Cronbach’s alpha of .765, which consisted of 4 items for assessing the perceived susceptibility and severity of COVID-19, 3 items for evaluating the perceived benefits of and 3 items for assessing barriers to a vaccination, and 2 items toward cues to action to receive a COVID-19 vaccine, 22 (3) the 12-items of the TPB scale that was evaluated in the previous study of Myers and Goodwin 18 composed one for assessing attitude, 5 items regarding subjective norms, 3 items toward the PBC, and 3 items about self-efficacy, and the final section for assessing the intention to get a future COVID-19 vaccine was measured by each item “If a COVID-19 vaccine is available, would you have it?”. The questionnaire was then pilot-tested for clarity and simplicity by 10 persons at a health center in Dong Thap province before distributing it to the community ( Appendix 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaire comprised 30 items, which was structured into four dimensions: (1) demographics of students such as age, gender, religion, education field, year of education, and source of information on COVID-19 vaccines; (2) Knowledge towards COVID-19 including ten items, which was developed and validated according to the study of Huynh G et al among healthcare workers and high-risk people which focused on Knowledge, Attitude, and Practices (KAP) related to COVID-19 in Vietnam; 12 , 21 (3) Attitudes regarding vaccination that consisted of 12 items using a 5-point Likert scale with responses ranging from strongly disagree through strongly agree. The instrument has been assessed as reliable and valid in previous studies with cronbach’s alpha being 0.765; 22 and (4) intention to receive a future COVID-19 vaccine was measured using item: “Will you intend to get a COVID-19 vaccination when it becomes available”, with responses yes or no being available. Participants who had answers of “no” to item of dimension 4 were asked an additional item explaining their reasoning for not accepting a vaccine ( Appendix 1 ).…”
Section: Methodsmentioning
confidence: 99%